2012
DOI: 10.1155/2012/464853
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception after Laparoscopic Gastric Bypass Surgery: An Underrecognized Complication

Abstract: Introduction. Intussusception after bariatric surgery is an uncommon complication that is now being frequently reported. Most people consider dysmotility to be the causative mechanism in the absence of obvious etiology. Material and Methods. A worldwide search identified literature describing intussusception after bariatric surgery. We also included our own patients and analyzed information regarding demographic profile, risk factors, presentation, diagnosis, and post treatment course. Results. Seventy one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 18 publications
(28 reference statements)
1
55
0
4
Order By: Relevance
“…After LRYGB, 0.1–0.3% of the patients will get an intussusception 6. Intussusception in pregnancy is rare, it accounts for 5% of all intestinal obstructions during pregnancy 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After LRYGB, 0.1–0.3% of the patients will get an intussusception 6. Intussusception in pregnancy is rare, it accounts for 5% of all intestinal obstructions during pregnancy 5.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the imaging properly, it is important to inform the radiologist about the anatomical situation after LRYGB. If there is still a suspicion of intussusception, a CT scan is the best modality to demonstrate intussusception 6. Radiation exposure to fetus and mother should be considered carefully, balanced against the condition of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…The largest review consisting of 71 patients, in which intussusception is found to be more common among female patients (98.6%) and most presented with abdominal pain and vomiting. Of these patients, 96% of patients required surgery, 70.6% of whom required anastomotic revision and 23.5% underwent reduction without resection [18].However, cases of spontaneous reduction in post gastric bypass patients presenting with intussusception is rarely found. The review focused on 23 patients with gastric bypass and presented with intussusception, 9 of the patients were found to have spontaneous reduction, although some were reduced while running the bowel intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article retrospectively identified 71 patients with intussusception after laparoscopic gastric bypass [5].…”
Section: Discussionmentioning
confidence: 99%